2014
DOI: 10.1378/chest.13-2442
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Characterization of Protracted Bacterial Bronchitis in Children

Abstract: Children with PBB are, typically, very young boys with prolonged wet cough and parent-reported wheeze who have attended childcare. Coupled with elevated NK-cell levels, the association between adenovirus and PBB suggests a likely role of viruses in PBB pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
2
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(175 citation statements)
references
References 39 publications
13
142
2
18
Order By: Relevance
“…10,11 İyi tedavi edilmeyen uzamış bakteriyel bronşit hastalarında, ilerleyen dönemlerde kronik süpüratif akciğer hastalığı ve bronşektazi gelişmektedir. 12 Çocuklarda uzamış bakteriyel bronşit ile ilgili az sayıda çalışma bulunmaktadır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…10,11 İyi tedavi edilmeyen uzamış bakteriyel bronşit hastalarında, ilerleyen dönemlerde kronik süpüratif akciğer hastalığı ve bronşektazi gelişmektedir. 12 Çocuklarda uzamış bakteriyel bronşit ile ilgili az sayıda çalışma bulunmaktadır.…”
Section: Discussionunclassified
“…10 Çalışmamızda hastaların ortanca yaşının 7 yıl bulunma nedeni olarak, üçüncü basamak bir merkez olan hastanemize başvurmadan önce farklı merkezlerde tedavi edilmeleri olarak düşünülmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several studies found that children developed chronic wet cough during their first two years of life, and were given the diagnosis protracted bacterial bronchitis around the age of two years (5,8,13), but the condition also occurs in older children (1, 7). There was a preponderance of boys in one study (13).…”
Section: Epidemiologymentioning
confidence: 99%
“…In one study, it was found in 74 % of children with this diagnosis (1,13,17). Tracheobronchomalacia predisposes to secretion accumulation, respiratory tract infections and cough, and may contribute to the development of bacterial bronchitis (1,17).…”
Section: Microbiology and Pathophysiologymentioning
confidence: 99%